2012
DOI: 10.3989/ajbm.2306
|View full text |Cite
|
Sign up to set email alerts
|

Paleobiology of the genus <i>Hypericum</i> (Hypericaceae): a survey of the fossil record and its palaeogeographic implications

Abstract: Genus Hypericum is one of the 100 largest genera in angiosperms with nearly 500 species. Despite its worldwide, nearly cosmopolitan distribution and apparently old age -there are fossil remains of relatives from the Mid Cretaceous -the fossil record of Hypericum has been largely overlooked in phylogenetic studies. Here, we survey the fossil record of Hypericum from the literature, with special emphasis on the oldest fossil remain, Hypericum antiquum, from which we reassess its diagnostic characters. We evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…S4.1), which employed a different set of fossils, and from a more comprehensive analysis of Malpighiales dating the crown group of the New World clade of Hypericum at 25 Ma (Xi et al, 2012), which is otherwise in agreement with our estimates for this node (29 Ma; HDP 23-33). Nürk et al's biogeographic reconstruction is also in conflict with the boreotropical hypothesis (stem lineages were reconstructed during the greenhouse period of the Eocene, including the EECO, in Africa) and in disagreement with the fossil record (Meseguer & Sanmartín, 2012) (see further discussion in Appendix S3).…”
Section: Geographic Projections Of These Climatic Preferences Show CLmentioning
confidence: 98%
See 1 more Smart Citation
“…S4.1), which employed a different set of fossils, and from a more comprehensive analysis of Malpighiales dating the crown group of the New World clade of Hypericum at 25 Ma (Xi et al, 2012), which is otherwise in agreement with our estimates for this node (29 Ma; HDP 23-33). Nürk et al's biogeographic reconstruction is also in conflict with the boreotropical hypothesis (stem lineages were reconstructed during the greenhouse period of the Eocene, including the EECO, in Africa) and in disagreement with the fossil record (Meseguer & Sanmartín, 2012) (see further discussion in Appendix S3).…”
Section: Geographic Projections Of These Climatic Preferences Show CLmentioning
confidence: 98%
“…out of 478) (Appendix 1 in Supplementary Information). Fossil data (14 records from the Late Eocene to the Oligocene; Appendix S2) were obtained from the literature (Meseguer & Sanmartín, 2012;Meseguer et al, 2015). A detailed discussion on the fossil record of Hypericum from Meseguer et al (2015) can be found in Appendix S3.…”
Section: Compilation Of Distributional and Climatic Datamentioning
confidence: 99%
“…Hypericum L. is the largest genus of the family Hypericaceae and includes 490 species of herbs, shrubs or trees distributed almost worldwide (Robson ). It is a relatively old genus dating back to the Early–Mid Tertiary (Meseguer and Sanmartín ).…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly distributed in the temperate regions of the Northern Hemisphere, but also in high‐altitude tropical and subtropical areas, and in a large variety of ecosystems (Meseguer et al 2013). Robson has prepared a detailed taxonomic treatment of the genus in a series of monographs (Robson 1977, 1981, 1985, 1987, 1990, 1996, 2001, 2002, 2006, 2010a, b, ). In these, the main diagnostic characters for the classification of the genus were identified, numerous new species were described and an infra‐generic classification into 36 sections was proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation